ANALISA SPASIAL UNTUK MELIHAT TINGKAT KESEJAHTERAAN MASYARAKAT DI PROVINSI BANTEN: Muhamad Jafar Elly, Reza Pahlevi - Jurnal, Redaksi Tim (PETIR, 2019)
Banten Province is an expantion area of the mother province, West Java. It is adjacent to the nation’s capital have an impact on the welfare of the surrounding community either in the district or municipality. So far, the data and information about the well-being of Banten area has not been distributed spatially. This is not less effective and informative when local government wants to make a policy that related to increased welfare at the district. This study was conducted to see the level of welfare in Banten through geographic information system approach. Data used in the process of spatial analysis includes the human development index, population density, dependency ratio and livelihood. The method used to process spatial analysis is weighted and overlay. The result of analysis showed that the average level of prosperity in Banten Province was in middle category which covers 116 districts out of the 155 districts spread across Banten. The rest was categorized quite high. The percentage of welfare level “Medium”and “High Enough” amounted to 74.83% and 25.17%. The sub districts have the status of “High Enough” majority owned by Tangerang district namely as many as 24 sub districts with 15.48%. These results are expected to be used as input for the Banten Provincial Government or the related parties in order to make a policies for improving the quality of life in society.